O corpo na arte da performance: artistas visuais e artistas da cena no Rio Grande do Sul - Londero, Alessandra Camargo (2014)
This paper presents a research on visual arts, specifically in the field of art and culture. It is based on an investigation that focuses the creative processes of visual artists and artists of the scene (dancers and actors) in the art of performance and its developments and reflections in the contemporary world. To do so, the research focuses on the understanding of the concept of performance art as a language in order to cast a look at the treatments given to the body by the performers and their creative processes. Thus, it begins with a historical survey about the beginning of performance, which appeared as an artistic genre in late '60s, emerging as a form of provocation and challenge. In this context, it is referred to the body-art as constituent parts of the work as well as it saw the passage of these bodies, before understood as tools, currently seen as subject-art. The Body as a reference point, with its images and expressions, is treated here as a reference in the language of the performances of the artists investigated. We chose to define the research on artists who develop performance art in Rio Grande do Sul state. These artists were nominated by their peers, artists and academics, which are connected directly to the study and research focused on the Art of Performance. Then, it is drawn a relationship between these artists and a parallel of the issues presented is carried out. In this dissertation, it is observed that the traffic of knowledge preserves its singularity, marking out territories with diluted borders in accordance with the creative and formative processes of artists. So, the performers have expressed their knowledge in understanding the art of performance, significantly diversifying their creative processes in this new world.